Linking reinforcement learning and cognitive maps to understand how the brain represents abstract tasks - Baram, A (2020)
The terms “reinforcement learning” (RL) and “cognitive maps” are both commonly rooted in early behaviourist psychology. However, in neuroscience, these two subfields have largely progressed in parallel. In this thesis, I use ideas and techniques from one subfield to address open questions in the other.